Characterization of psychrotrophic bacterial communities in modified atmosphere-packed meat with terminal restriction fragment length polymorphism - Nieminen, T.T.; Vihavainen, E.; Paloranta, A.; Lehto, J.; Paulin, L.; Auvinen, P.; Solismaa, M.; Björkroth, K.J. (International journal of food microbiology, 2011)
Characterization of psychrotrophic lactic acid bacteria (LAB) and Brochothrix thermosphacta communities is needed to understand the microbial ecology of spoilage of modified atmosphere-packed (MAP) meats. To overcome the limitations of the currently used methods for the characterization of psychrotrophic bacterial communities in meat, we developed a culture-independent, 16S rRNA gene-targeted terminal restriction fragment length polymorphism (T-RFLP) method. An identification library consisting of 100 Gram-positive and 30 Gram-negative meat-associated bacterial strains was set up to identify the terminal restriction fragments derived from the communities. The taxonomic resolution level of the T-RFLP method was in between genus and species within the investigated LAB strains and within family and genus within the investigated Gram-negative strains. The established library was applied to identify the members of bacterial communities in MAP minced meat at the end of the shelf life. The T-RFLP results and plate counts on Man-Rogosa-Sharpe, Violet Red Bile Glucose, and Streptomycin sulfate thallium acetate actidione agars indicated that LAB and B. thermosphacta predominated in meat. The bacterial taxa associated with the T-RFLP results were compared to those identified among plate-grown LAB isolates by numerical ribopattern analysis. Both methods agreed that Leuconostoc spp. and Carnobacterium spp. prevailed in the LAB community in minced meat followed by Lactobacillus algidus, Lactococcus spp. and Weissella spp. Colony identification revealed that Leuconostoc gasicomitatum, L. gelidum, Carnobacterium divergens and C. maltaromaticum were the predominant LAB species. The T-RFLP results were shown to correlate with viable counts of Leuconostoc spp. and B. thermosphacta. The T-RFLP method was found to be a useful tool enabling rapid and high-throughput characterization of psychrotrophic bacteria prevailing in MAP meat. ► Leuconostoc gasicomitatum, L. gelidum and Carnobacterium divergens prevailed in meat. ► The bacteria found in meat by colony identification were also found by T-RFLP. ► T-RFLP results correlated with viable counts of Leuconostoc spp. and Brochothrix thermosphacta. ► T-RFLP was a useful tool for characterization of bacterial communities in meat.